Caries intensity and Streptococcus mutans in the saliva of patients with Turner syndrome - Aida Kusiak; Barbara Kochańska; Dariusz Świetlik; Aleksandra Cydejko; Adrian Maj (Elsevier, 2021)
Aim: The aim of this study was to evaluate the caries intensity and Streptococcus mutans (SM) counts in patients with Turner syndrome. Materials and methods: Nineteen patients aged 20-40 years were clinically and cytogenetically diagnosed with Turner syndrome (45, X). The karyotype was determined by chromosome analysis of peripheral blood lymphocytes. The control group comprised 47 healthy women aged 21-40 years. Both groups included non-smokers with no specific diet, such as a vegetarian or vegan diet, who were generally healthy with good oral hygiene and periodontal condition. Patients treated with antibiotics or steroid preparations in the past 6 months or with diseases or conditions that might affect the oral mucosal environment, such as disorders of salivary secretion and diabetes, were excluded from the study. Decayed, missing, and filled teeth (DMFT) scores and SM counts in saliva were determined. Results: No colony growth of SM was noticed in 53% of patients with Turner syndrome and 4.2% of controls (p < 0.001). Colony counts of SM ≥ 105 in saliva were observed in none of the patients with Turner syndrome but in 66% of controls (p < 0.001). The mean DMFT score was 1.63 ± 2.52 in patients with Turner syndrome and 14.49 ± 6.88 in controls. Statistically significant differences between the two groups were observed (p < 0.05). Conclusion: Patients with genetic disorders may have different severities of caries and SM counts in saliva compared to those without genetic disorders. Further studies on saliva properties and genes located on the X chromosome could contribute to determining the effect of the X chromosome on the pathological processes in the oral cavity.